PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH MELALUI PENDEKATAN INKUIRI TERBIMBING TERHADAP MOTIVASI DAN HASIL BELAJAR KIMIA - Roewijadi, .; Siregar, Tiurlina (Magister Pendidikan IPA, UNCEN, 2015)
This study aims to determine the difference in learning motivation and learning outcomes among students who are applied chemistry model of problem-based learning through guided inquiry approach and students who are applied conventional learning. This study was conducted using a quasi-experimental design involving the treatment group and the control group research design using the non-equivalent control group design. The independent variable in this study is the application of problem-based learning model through guided inquiry approach and the dependent variable is the motivation to learn and student learning outcomes. The population in this study were students of class X MIPA SMA Negeri 1 Merauke in the academic year 2014/2015. Samples are class X MIPA-5 as the control classes and class X MIPA-6 as an experimental class with the number of students in each grade at which 45 students. The results of the study showed that there are significant differences which in the value of n-Gain an average of the control class 0,38 and an experimental class 0,70. Based on the data results processing by using SPSS 16.0 programe was gained value Sig. (2-tailed) = 0,000 < 0,05 so that H0 was refused and Ha was accepted. This means that the application of problem-based learning model through guided inquiry approach gives a positive difference to the motivation and learning outcomes chemistry in class X MIPA SMA Negeri 1 Merauke in the academic year 2014/2015. The application of problem-based learning model through guided inquiry approach can be a good choice in determining the learning model that will be used in the classroom. Keywords : Problem Based Learning Model, Guided Inquiry Approach, Study Motivation, Learning Outcomes, Concepts Redox Reactions, SMA Negeri 1 Merauke.